2015
DOI: 10.1002/acp.3131
|View full text |Cite
|
Sign up to set email alerts
|

Age Differences in Learning from Instructional Animations

Abstract: The present study tests the effects of the decline of executive functions and spatial abilities with aging on the comprehension of a complex instructional animation. An animation of a piano mechanism was presented individually to 33 young adults and 31 elderly participants. Two presentation speeds of the animation (normal and slow) were compared in a 2 × 2 experimental design. Eye movements were recorded during the learning time. Then, four executive function tests (inhibition, shifting, updating, and processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Four of the reviewed studies examined learners' visual attention to animations presented at different speeds. Three of them revealed that different animation speeds influenced learners' gaze behaviours (Boucheix et al, 2015;Schmidt-Weigand et al, 2010a, Experiment 2;…”
Section: Type Of Animation Presentationmentioning
confidence: 99%
See 4 more Smart Citations
“…Four of the reviewed studies examined learners' visual attention to animations presented at different speeds. Three of them revealed that different animation speeds influenced learners' gaze behaviours (Boucheix et al, 2015;Schmidt-Weigand et al, 2010a, Experiment 2;…”
Section: Type Of Animation Presentationmentioning
confidence: 99%
“…Like Alemdag and Cagiltay's (2018) study, individual differences were examined as a new theme, even though that is one of the multimedia principles. Prior knowledge (Köseo glu et al, 2013;Kragten et al, 2015;O'Keefe et al, 2014), spatial ability (Boucheix et al, 2015;Chen et al, 2015;Kühl et al, 2018), age (Boucheix et al, 2015;Pavlin et al, 2019), and educational background (Pavlin et al, 2019) are the four sub-factors that shape individual differences.…”
Section: Individual Differencesmentioning
confidence: 99%
See 3 more Smart Citations